Prevalence of Diabetic Peripheral Neuropathy among Type I Diabetes – An Observational Study - C.V. , Senthilnathan; Paul, Jibi; M. , Manoj Abraham; M. , Sasirekha (International Journal of Psychosocial Rehabilitation, 2020)
Objective: The objective of this study is to find out the prevalence of diabetic peripheral neuropathy (DPN) among diabetics in Chennai.Background of the Study: DPN is the most common chronic and long-term complication of diabetes mellitus and is considered the leading cause of mortality and morbidity rate, causing a huge economic burden to the government. It is one of the serious microvascular complications of DM, which has been diagnosed in 20-50% of the diabetic population.Methodology: This is a cross-sectional study with 100 patients selected by the simple random sampling method. Those who were aged more than 30 years and diagnosed positive for type I diabetes for at least 1 year duration with random blood sugar >200 mg/dl as per Indian Council of Medical Research guidelines 2005. Those who were willing to participate and who had regular follow-up visits for at least 6 months were included in this study. The exclusion criteria are those who have type 1 diabetes, gestational DM, and maturity-onset diabetes of the young; significant musculoskeletal disorder in the lower limb; those who underwent amputation of the whole foot, below-knee amputation, and above-knee amputation; and peripheral neuropathy due to any other cause. The prevalence of DPN among diabetics in Chennai will be found out. Pre- and post-tests were done using the DN4, S-LAANS, and MNSI questionnaires.Result: The study was conducted in type 1 diabetes patient following results were obtained The prevalence was found using the DN4, MNSI, and S-LANSS questionnaires. The mean of DN4 was found to be 4.0800, and it's significant with p